2015
DOI: 10.1159/000381733
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Thromboelastometry as a Predictor of Transfusion Requirements during Adult Living Donor Liver Transplantation

Abstract: Background: The ability to predict transfusion requirements may improve perioperative bleeding management as an integral part of a patient blood management program. Therefore, the aim of our study was to evaluate preoperative thromboelastometry as a predictor of transfusion requirements for adult living donor liver transplant recipients. Methods: The correlation between preoperative thromboelastometry variables in 100 adult living donor liver transplant recipients and intraoperative blood transfusion requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 87 publications
0
45
0
Order By: Relevance
“…Viscoelastic haemostatic assays have a better predictive value for bleeding in liver disease (Fayed et al , ; Tafur et al , ; Pustavoitau et al , ) and re‐bleeding than SLTs (Chau et al , ). A retrospective, single centre study comparing SLT and ROTEM in post‐operative bleeding in adult liver transplant (LT) patients found that several ROTEM parameters predicted bleeding (cut‐offs shown in brackets): EXTEM CT (≥65 s), INTEM CFT (≥181 s), FIBTEM A10 (≤13 mm) and FIBTEM MCF (≤15 mm) (AUC 0·682, 0·615, 0·615 and 0·611 respectively) compared to no SLT tests (Dotsch et al , ).…”
Section: Liver Disease and Liver Surgerymentioning
confidence: 99%
“…Viscoelastic haemostatic assays have a better predictive value for bleeding in liver disease (Fayed et al , ; Tafur et al , ; Pustavoitau et al , ) and re‐bleeding than SLTs (Chau et al , ). A retrospective, single centre study comparing SLT and ROTEM in post‐operative bleeding in adult liver transplant (LT) patients found that several ROTEM parameters predicted bleeding (cut‐offs shown in brackets): EXTEM CT (≥65 s), INTEM CFT (≥181 s), FIBTEM A10 (≤13 mm) and FIBTEM MCF (≤15 mm) (AUC 0·682, 0·615, 0·615 and 0·611 respectively) compared to no SLT tests (Dotsch et al , ).…”
Section: Liver Disease and Liver Surgerymentioning
confidence: 99%
“…1, 2; table 1) [4]. In bleeding patients, a cut-off value of < 75 s seems to be an adequate value to prevent coagulopathic bleeding [27]. …”
Section: Bleeding Management In Patients With End-stage Liver Diseasementioning
confidence: 99%
“…Fayed and associates 14 demonstrated that most ROTEM variables can accurately predict packed RBCs, fresh frozen plasma, cryoprecipitates, and platelet transfusion needs; however, this test is expensive and is not routinely performed before liver transplant. More economic models for prediction of blood loss risk are needed as they are more practical and cost effective.…”
Section: Discussionmentioning
confidence: 99%